Two Optimal Inequalities Related to the Sándor-Yang Type Mean and One-Parameter Mean (Communications in Mathematical Research, 2021)
In this paper, we establish two optimal the double inequalities for Sándor-Yang type mean and one-parameter mean.
Keywords: Sándor-Yang type mean; $p$-th one-parameter mean; Neuman-Sándor mean; second Seiffert mean; inequality.